2020
DOI: 10.3390/nu12102990
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Strategies in Prediabetes: A Scoping Review of Recent Evidence

Abstract: Nutritional therapy has been conventionally recommended for people with prediabetes as a method to delay or halt progression to type 2 diabetes. However, recommended nutritional strategies evolve over time. Hence, we performed a scoping review on recently reported nutritional interventions for individuals with prediabetes. Ovid MEDLINE, PubMed, Embase, Scopus, CINAHL and PsycINFO databases were searched to identify relevant research articles published within the past 10 years. Ninety-five articles involving a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 128 publications
(530 reference statements)
0
14
0
Order By: Relevance
“…In general, intervention studies examining the effects of dairy intake suggest favorable effects on vascular function. A recent scoping review reported that proteins derived from milk are common interventions for prediabetes and that significant improvements in brachial artery flow-mediated dilation and oxidative stress markers are observed without any evidence to support the benefit of milk proteins on insulin or lipid profiles [ 104 ]. In the early stages of atherosclerosis, damage to vessel walls can be protected by milk-derived bioactive peptides, which have anti-inflammatory effects on endothelial cells [ 105 ].…”
Section: Vascular Function and Dairymentioning
confidence: 99%
See 2 more Smart Citations
“…In general, intervention studies examining the effects of dairy intake suggest favorable effects on vascular function. A recent scoping review reported that proteins derived from milk are common interventions for prediabetes and that significant improvements in brachial artery flow-mediated dilation and oxidative stress markers are observed without any evidence to support the benefit of milk proteins on insulin or lipid profiles [ 104 ]. In the early stages of atherosclerosis, damage to vessel walls can be protected by milk-derived bioactive peptides, which have anti-inflammatory effects on endothelial cells [ 105 ].…”
Section: Vascular Function and Dairymentioning
confidence: 99%
“…The available studies investigating dairy-derived proteins suggest a cardioprotective effect in preclinical populations. For instance, proteins derived from milk are common interventions for prediabetes since significant improvements have been observed in oxidative stress markers and glucose metabolism, especially postprandial glucose and glycated hemoglobin A1c (HbA1c), without any improvements of insulin profiles [ 104 ]. A proprietary whey protein hydrolysate that contained bioactive peptides with α-glucosidase-inhibiting properties reduces postprandial hyperglycemia in prediabetes adults [ 124 ].…”
Section: Mechanisms Of Improvement Induced By Dairy Intakementioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, a large number of studies suggest that lifestyle changes (increased physical activity, adherence to a healthy diet, avoidance of smoking, and maintenance of an adequate body weight) might help to prevent the onset of both conditions [ 4 ]. Concerning dietary interventions, there is compelling evidence that food ingredients might have an impact on glucose regulation, as some food components improve β-cell function, insulin sensitivity, glycaemic control, or oxidative stress [ 5 ]. In this regard, frequent intake of red meat and processed meat has been associated with an increased risk of developing T2DM, whereas whole-grain and fibre intake has showed an inverse association with T2DM incidence [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…A healthy diet and regular physical activity are both powerful tools in terms of primary prevention, becoming first-line treatments when a metabolic disease occurs [ 1 ]. Thus, nutritional health is nowadays a major issue for the general population and, even more, for high-risk subsets of individuals [ 2 ].…”
Section: Introductionmentioning
confidence: 99%